2014
DOI: 10.1128/aac.02886-14
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Transmission of Multidrug-Resistant Organisms during Catheter Exchange using Antimicrobial Catheters

Abstract: Exchange with CHX-M/R CVCs completely prevented cross-contamination by MRSA, P. aeruginosa, and C. albicans biofilms (P < 0.0001). Furthermore, CHX-M/R CVCs were superior to M/R CVCs against P. aeruginosa and C. albicans (P ‫؍‬ 0.003) and were superior to CHX/SS CVCs against MRSA and P. aeruginosa (P ‫؍‬ 0.01). In conclusion, exchange with the novel CHX-M/R CVC was the only exchange effective in completely and concurrently preventing cross-contamination from bacteria and Candida.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Catheter‐related complications, such as malfunction and displacement, and patient/family preferences are also indications for GCE. Different studies performed in adult populations have suggested that GCE is associated with a low complication rate and without an increased risk of infection . However, these findings have not been confirmed in children with malignancies.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…Catheter‐related complications, such as malfunction and displacement, and patient/family preferences are also indications for GCE. Different studies performed in adult populations have suggested that GCE is associated with a low complication rate and without an increased risk of infection . However, these findings have not been confirmed in children with malignancies.…”
Section: Introductionmentioning
confidence: 69%
“…evaluated prospectively the usefulness of GCE for the treatment of infected CVCs in 17 patients undergoing HSCT or intensive chemotherapy and concluded that GCE during adequate antimicrobial therapy may be a reasonable option for the treatment of CLABSI when antimicrobial therapy alone has been unsuccessful. Some studies have suggested that GCE with antibiotic‐coated CVCs could prevent CLABSI and be an alternative for removing the CVC and de novo insertion . Minocycline/rifampin‐coated CVCs have been used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Stocco et al (2016), depending on the tested micro-organism, there will be a short time to CVC colonization. Two in vitro studies of Jamal et al (2014aJamal et al ( , 2014b informed that CHX/ SS-coated CVCs were not as effective in inhibiting biofilm colonization by several resistant Gram-negative and Gram-positive bacteria, including K. pneumoniae, as CHX/M-R (minocycline-rifampin). The authors considered that the CHX-M/R catheters exhibited better antimicrobial durability and were more effective than CHX/SS among others.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, CHX-M/R CVCs showed superior activity against P. aeruginosa and C. albicans to M/R catheters and were superior to CHX/SS CVCs against MRSA and P. aeruginosa ( Jamal et al 2014 ).…”
Section: Prevention Of Clabsismentioning
confidence: 99%